PENGENCER SEMEN YANG DIPERKAYA MINYAK IKAN MENJAGA KUALITAS SPERMATOZOA BABI (Sus scrofa domesticus) SELAMA PENYIMPANAN JANGKA PENDEK Fish Oil Enriched Semen Extender Protect Boar (Sus scrofa domesticus) Spermatozoa Quality During Short Term Storage - Parsaoran Silalahi; Pohan Panjaitan; Imelda Tafonao (JURNAL NUKLEUS PETERNAKAN, 2026)
This study aimed to evaluate the effect of fish oil addition to semen extender on the quality of boar spermatozoa during 24-hour storage at 15°C. Fresh semen was collected from a healthy adult boar with initial motility ≥70% and diluted using a glukosa–sitrat–EDTA extender supplemented with 0 g (P0), 0.15 g (P1), 0.30 g (P2), and 0.45 g (P3) of fish oil per 1.000 mL. The experiment was arranged in a completely randomized design (CRD) with four treatments and four replications. Parameters observed included motility, viability, abnormality, and semen pH after 24-hour storage. Analysis of variance showed that fish oil addition had a highly significant effect (P<0.01) on sperm viability, but no significant effects (P>0.05) on motility, abnormality, or pH. The highest viability was found in P1 (93.25%) and the lowest in P3 (82.00%). Motility and abnormality improved at low doses but declined at higher concentrations. The pH values remained stable (6.7–7.2) across all treatments. In conclusion, adding a low dose of fish oil (0.15 g/1.000 mL) effectively maintained spermatozoa quality without altering extender chemistry, suggesting its potential as a natural additive for semen extender formulations in tropical artificial insemination programs.